Performances and procedures modules in micro electro mechanical system packaging technologies - Amiri, Iraj Sadegh; Ariannejad, Mohammad Mahdi; Vigneswaran, Dhasarathan; Lim, Chin Seong; Yupapin, Preecha Promphan (Elsevier, 2018)
This paper presents the challenging issues in micro electro mechanical system (MEMS) packing technologies. The MEMS package includes a MEMS device and a signal conditioning electronic circuit. In one viewpoint, MEMS application is categorized by the type of sensor, actuator, and structure. MEMS technology applications in general domains are automotive, consumer, industrial, biotechnology and commercial applications. Few methods such as the low power oven, vacuum, and silicon glass packages were discussed. The major technique as die level and wafer level of packing including thin-film packing were reviewed in this paper. The problem of several failure mechanisms and challenges and their solutions were discussed in this review.